IMPACT OF ACCOUNTING MEASUREMENT ACCORDING TO RELATIVE IMPORTANCE IN THE QUALITY OF FINANCIAL STATEMENTS - Israa Mohanad Abdul Melek Ahmed; Dhabya Safaa Mahmood (Scholars Digest Publishing, 2024)
Accounting measurement (quantitative and monetary measurement) is the essence of the accounting process because it works to record, classify, relay, and then summarize all the operations and events experienced by the organization and show them in their final form (The outcome of the accounting process), which represents the elements of the financial statements, the latter of which contain credible accounting information. clarity, relevance, accuracy, and comparability. It is useful and important for internal users and external users in the process of making appropriate decisions that differ from one party to another according to their organizations’ need for accounting information. Therefore, it is not possible to understand accounting fully and correctly without understanding what is measured and how to measure it. The accountant must consider the importance of these accounting elements and information contained in the financial statements because their deletion or any error affects the decision-making processes of internal and external users.
Keywords: accounting measurement, financial statements, relative importance, accounting information, internal and external users.